Knee dynamic analysis based on 2D-to-3D registration of fluoroscopic and angiographic images / Amir Hossein Saveh ... [et al.] - Saveh, Amir Hossein; Kazemi, Seyyed Morteza; Yussof, Hanafiah; Katouzian, Hamid Reza; Vanat, Qureish; Chizari, Mahmoud (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2012)
This paper introduces a method to measure the kinematics of the knee using fluoroscopic imaging. The method involves two stages. In the first, the knee joint is recorded during normal gait by fluoroscopy using a mobile C-arm and an angiographic imaging system. The images then were processed to calculate the two-dimensional (2D) kinematics of the joint during the different phases of the gait cycle. This was then used to calculate three-dimensional (3D) kinematics of the joint. In parallel the reaction force on the knee joint was calculated using gait lab analysis. In the second stage, the 3D finite element model of the knee was created using computerised tomography (CT) and magnetic resonance imaging (MRI) data. The model was then used to analyse the joint contact loads during the gait cycle based on the input data obtained from the kinematic and reaction force data from stage one. This allowed the analysis of the mechanical behaviour of the knee and thus the stress distribution on the medial and lateral compartments of the knee.